The efficacy in treatment of facial melasma with thulium 1927-nm fractional laser-assisted topical tranexamic acid delivery: a split-face, double-blind, randomized controlled pilot study - Rungsima Wanitphakdeedecha (2020)
© 2020, Springer-Verlag London Ltd., part of Springer Nature. This split-face, double-blind, randomized controlled study examines the efficacy of fractional thulium laser (FTL)–assisted delivery of topical tranexamic acid (TXA) compared with FTL alone as a treatment option for melasma. Forty-six adults with Fitzpatrick skin types III–V and recalcitrant melasma underwent four weekly treatments with fractional 1927-nm thulium laser on both sides of the face. Immediately after treatment, TXA was applied to one side of the face and normal saline solution (NSS) to the contralateral side as control under occlusion. Melanin index (MI), modified MASI (mMASI), and patients’ self-assessed improvement scores were measured at baseline, 1 week, 4 weeks, and 3- and 6 months after the final treatment and were examined statistically with a paired sample t test with significance set at p ≤ 0.05. The majority of the participants (95.7%, n = 44) were female with Fitzpatrick skin type IV (82.6%) and a mean age of 48.0 ± 10.0 years. Twenty-nine individuals were able to be followed up until the 6-month assessment. Significant improvement from baseline was seen in both the MI and mMASI scores for both the TXA and control sides at 3 months, with no statistically significant difference between sides. By the 6th month, significant differences in MI and mMASI scores from baseline were still noted, except in the MI for controls. The patients’ self-assessment showed similar patterns. No serious adverse events were reported for either group. A regimen of FTL-assisted delivery of TXA over a 4-week period is a safe and effective treatment option for melasma, producing significant improvement up to 3 months. Results further would suggest a repeat regimen every 3 months could be useful for treatment of recalcitrant melasma.